Settleable atmospheric dust and ambient noise: case study in the central area of Tacna during the COVID-19 pandemic - Coaquira Canllahui, Kyra Rocío (2023)
The concentration of Settleable Atmospheric Dust (SAD) and the ambient noise were monitored and evaluated in the downtown area in the city of Tacna. The objective was to determine if the obtained values exceeded the recommendations by the World Health Organization for atmospheric dust (0.5 mg/cm2/30 days), and the National Environmental Quality Standards for noise. Four monitoring stations were installed to assess SAD using the receptor plate method. The noise monitoring was conducted at nine points following the National Protocol for Ambient Noise Monitoring. It was found that all monitored points exceeded the National Environmental Quality Standards for noise, and no statistically significant differences were found between the concentrations of atmospheric dust nor the noise measurements in the years 2017 and 2021. Therefore, it can be concluded that the recorded values before and during the pandemic did not significantly differ.